Green Marketing Strategy Adoption by Indian Political Party Brands with Special Emphasis on Marketing Mix - Yadav, Parul; Agarwal, Bhawna; Mathew, Jones (Indian Journal of Marketing, 2023)
Purpose : The goal of this paper was to provide an overview of the green marketing mix of political party brands and to explain how Indian political brands are implementing green marketing strategies along with the marketing mix consisting of the seven Ps for political party brands. Methodology : The paper is theoretically positioned and qualitative in nature. Findings : We discovered that very few papers have investigated this topic. Neither green marketing nor political marketing researchers have identified the green marketing positioning strategy of political brands, nor have political marketing researchers focused on the seven Ps of a political brand. Political parties are implementing green marketing strategies in practice, but academics provide no evidence of this. Practical Implications : Following a thorough literature review, we concluded that political marketers or managers should continue exploring new voter segments, such as green voters. We advise researchers to focus on this area of marketing so that voter behavior can be studied more scientifically. Our study has limitations and leaves room for future researchers. More examples of green initiatives can be found while broadening the scope of research to include other countries. Originality : Unlike prior research in the green and political marketing domain, the current work has paid attention to non-conventional political marketing strategies. Development of the seven Ps concept is also undertaken for the first time.